Hyperemia-Related Changes in Arterial Stiffness: Comparison between Pulse Wave Velocity and Stiffness Index in the Vascular Reactivity Assessment - Juan Torrado; Daniel Bia; Yanina Zócalo; Ignacio Farro; Federico Farro; Ricardo L. Armentano (International Journal of Vascular Medicine)
Carotid-to-radial pulse wave velocity (PWVcr) has been proposed to evaluate endothelial function. However, the measurement of PWVcr is not without limitations. A new simple approach could have wide application. Stiffness index (SI) is obtained by analysis of the peripheral pulse wave and gives reproducible information about stiffness of large arteries. This study assessed the effects of hyperemia on SI and compared it with PWVcr in 14 healthy subjects. Both were measured at rest and during 8 minutes after ischemia. SI temporal course was determined. At 1 minute, SI and PWVcr decreased (5.58±0.24 to 5.34±0.23 m/s, P<0.05; 7.8±1.0 to 7.2±0.9 m/s; P<0.05, resp.). SI was positively related to PWVcr in baseline (r=0.62 , P<0.05), at 1 minute (r=0.79, P<0.05), and during the whole experimental session (r=0.52, P<0.05). Conclusion. Hyperemia significantly decreases SI in healthy subjects. SI was related to PWVcr and could be used to facilitate the evaluation of hyperemia-related changes in arterial stiffness.